High In-Vitro Antitumour Activity of Triphenyltin Coumarin 3-Carboxylate and its Coordination Complexes With Monodentate Oxygen Donor Ligands Against the Epstein Barr Virus (EBV)-DNA Positive Raji and the P-388 Murine Leukaemia Cell Lines, and Evidence for the Suppression by Organotin of the Early Antigen Complex in the EBV Lytic Cycle. - Koshy, Joyce; Das, V.G.; Balabaskaran, S.; Ng, S.W.; Wahab, Norhanom (Hindawi Publishing Corporation, 2000)
Triphenyltin coumarin-3-carboxylate and its coordination complexes with ethanol, triphenylphosphine oxide, triphenylarsine oxide, diphenylcyclopropenone and quinoline N-oxide exhibited high in vitro cytotoxicity (LC(50) values in the range 0.25-3.4 mug/mL) when tested against EBV-DNA positive Raji cells and P-388 leukaemia cells, compared to the standard drug 5-Fluorouracil, which showed LC(50) values of 11 and >50 mug/mL, respectively, against these cells. Additional tests performed on the Raji cells incubated with the quinoline N-oxide complex in the presence of the tumour promoters, TPA and sodium butyrate, revealed that the diffused and restricted protein components of the early antigen complex were suppressed relative to the control containing only the promoters, indicating impaired function of the genes involved as transactivators in the early lytic cycle of the EBV. The failure of the restriction enzymes Eco R1 and Hind III to cleave the extracted DNA from such treated cells in contrast to the control, coupled with the amplification of the BMLF-1 gene by the PCR technique which was realised only with the DNA of the control and not of the treated sample, point to a punitive interaction of the organotin with the nuclear DNA of the Raji cells.